Enterprise logic: explaining corporate attention to stakeholders from the ‘inside‐out’ - Crilly, Donal; Sloan, Pamela (Strategic Management Journal, 2012)
Why are some firms more effective than others at addressing stakeholder concerns? Conventional stakeholder theories focus on variables in the external environment and cannot adequately explain variance across firms operating in the same context. Our matched‐pair study of eight global corporations goes inside the firm and investigates the role of managerial cognition on corporate attention to stakeholders. We find that top management's conceptualization of the firm's relationship with society—which we name enterprise logic—prompts distinct foci of attention and potentially constrains how well a single firm can simultaneously attend to multiple stakeholders. These findings highlight the value of an ‘inside‐out’ perspective, centered on managerial cognition, in explaining why some firms address stakeholder concerns more effectively than their peers. Copyright © 2012 John Wiley & Sons, Ltd.